Conduction Mechanism and Charge Transporting Property of Te90-xSe10Cdx Chalcogenides by AC Conductivity and Dielectric Analysis. (2018) - Kumar Verma, Arvind; Chandra, Pramesh; Kumar, Nishant; Srivastava, Anchal; R.K.Shukla,
Abstract: The effects of Cd incorporation on the dielectric properties of chalcogenide alloy Te90-x Se10 Cdx ( x = 0, 10, 15, 20 at. wt.%) have been studied. These are synthesised by melt quenching technique. Frequency dependence of the AC conductivity, dielectric constants (ε′), dielectric losses (ε′′) and dissipation factor in the frequency range 50Hz -5 MHz at room temperature have been reported. Temperature dependent studies in 298 – 473 K at a fixed audio frequency of 10 kHz have also been measured. It is found that AC conductivity, dielectric loss and dissipation factor increase as frequency and temperature increase. Dielectric constant decreases as frequency increases whereas it increases with increasing temperature. Dielectric constant increases while dielectric loss decreases with increasing Cd content in Te-Se matrix. Possible explanations of metal (Cd) induced effects on the conduction mechanism of the Te90 Se10 alloy are discussed.